Accessory to war : the unspoken alliance between astrophysics and the military - Tyson, Neil deGrasse (W.W.Norton and Company, 2018)
"An exploration of the age-old complicity between skywatchers and warfighters, from the best-selling author of Astrophysics for People in a Hurry. In this fascinating foray into the centuries-old relationship between science and military power, acclaimed astrophysicist Neil deGrasse Tyson and writer-researcher Avis Lang examine how the methods and tools of astrophysics have been enlisted in the service of war. "The overlap is strong, and the knowledge flows in both directions," say the authors, because astrophysicists and military planners care about many of the same things: multi- spectral detection, ranging, tracking, imaging, high ground, nuclear fusion, and access to space. Tyson and Lang call it a "curiously complicit" alliance. Spanning early celestial navigation to satellite-enabled warfare, Accessory to War is a richly researched and provocative examination of the intersection of science, technology, industry, and power that will introduce Tyson's millions of fans to yet another dimension of how the universe has shaped our lives and our world."--Provided by publisher.